"He Won't Get Anything Out of This!" Intersections of Race, Disability, and Access. (March 2016) - Theoharis, George; Causton, Julie
This case describes the leadership role and challenges in moving a school in a more inclusive direction for students with disabilities. Assistant Principal Mosier plays a key role and in that role meets Charles, sixth grader, who has been educated in self-contained special education. While 58% of the students at Reynolds are African American and 35% are White, all 12 of the students in Charles's class are African American. As Charles began seventh grade, Reynolds adapted a more inclusive service delivery with general and special educators co-planning and co-delivering instruction. This case focuses on the intersection between race and disability in the midst of a school's effort to create more inclusive services delivery.